New records of ciliate epibionts (Ciliophora: Suctorea) from Brunei Darussalam. (20th August 2014) - Chatterjee, Tapas; Fernandez-Leborans, Gregorio; Marshall, David J.
Abstract : The present study reports on range extension of the suctorian species Praethecacineta halacari and Thecacineta calix to the region of Brunei Bay, Brunei Darussalam, Borneo.